Solid Primary Retroperitoneal Masses in Adults: An Imaging Approach - Gulati, Vaibhav; Swarup, M. Sarthak; Kumar, Jyoti (Indian Journal of Radiology and Imaging, 2022)
Mass lesions in the retroperitoneal space may be primary or secondary. Primary retroperitoneal mass lesions are relatively uncommon as compared to pathology that arises secondarily from retroperitoneal organs. These may be solid or cystic lesions. The overlapping imaging features of various solid primary retroperitoneal tumors make the diagnosis difficult, and hence, histopathology remains the mainstay of diagnosis. This paper provides a brief review of the anatomy of the retroperitoneal space and provides an algorithmic approach based on cross-sectional imaging techniques to narrow down the differential diagnosis of solid primary retroperitoneal masses encountered in the adult population.
Keywords: Retroperitoneal space; Anatomy; Imaging; Solid; Algorithmic approach